Oxidation-absorption process for simultaneous removal of NOx and SO2 over Fe/Al2O3@SiO2 using vaporized H2O2. (March 2022) - Jia, Shuaihui; Pu, Ge; Gao, Jie; Yuan, Cong
Abstract: 3% Fe/Al2 O3 and 3% Fe/Al2 O3 @SiO2 were prepared to investigate the performance in simultaneous removal of NOx and SO2 using vaporized H2 O2 . Certain paraments were changed to explore the activity of catalysts, including temperature, H2 O2 concentration, GHSV and coexistence gases component. A 24-h durability test was conducted on 3% Fe/Al2 O3 @SiO2 . Moreover, a series of characterizations were employed to analyze the physical and chemical properties of catalysts, including XRD, BET, SEM, TEM, FTIR and XPS. Compared with 3% Fe/Al2 O3, 3% Fe/Al2 O3 @SiO2 exhibited more excellent catalytic activity, which could achieve the peak removal efficiency of 100% for SO2 and 93.76% for NOx . Moreover, 3% Fe/Al2 O3 @SiO2 kept stable simultaneous removal efficiency in a 24-h test. The characterization results indicated that the BET area was greatly improved and the core-shell structure was synthesized with the formation of more micropores and mesopores by the coating of SiO2, which could improve the activity of catalyst at high temperature and high SO2 concentration. Besides, the mechanism of SO2 molecules on simultaneous removal was investigated. On one hand, a part of H2 O2 was consumed by SO2 molecules without catalyst, which resulted in the drop of NOx removal by the decrease of oxidants. The main products were sulfites and bisulfites, which were broken down into SO2 over the catalyst. On the other hand, the presence of SO2 was beneficial for NOx removal by increasing oxygen vacancies on the catalyst surface and facilitating the absorption of NO2 by NaOH solution. Graphical abstract: Image 1 Highlights: Removal efficiency of 93.76% for NOx was obtained on 3% Fe/Al2 O3 @SiO2, higher than 3% Fe/Al2 O3 . The activity of catalyst was significantly improved by the coating of SiO2 at high temperature and high SO2 concentration. NOx removal efficiency kept stable in a 24-h test. The effect of SO2 on simultaneous removal was investigated in detail.